Managerial Finance / With Tax Update: Eighth Edition - Copeland Thomas E; Fred Weston J (The Dryden Press, 1989)
Fundamental Concepts of Managerial Finance, The Finance Function, Financial Statements, The Financial Environment, The Tax Environment, The Time Dimension in Financial Decisions, The Time Value of Money, Capital Budgeting Techniques, How the Market Determines Discount Rates, Financial Analysis and Planning and Control, Financial Ratio Analysis, Financial Planning and Control, Financial Forecasting, Working Capital Management, Working Capital Policy, Cash and Marketable Securities Management, Inventory Management, Credit Management and Policy, Short-Term Financing, Decision Making Under Uncertainty, Risk and Return: Theory and Evidence and Applications, Options on Risky Assets, Cost of Capital and Valuation, Financial Structure and the Cost of Capital, Capital Structure and the Cost of Capital, Valuation, The Treasurer's Point of View: Policy Decisions, Common Stock Financing, Lease Financing, Warrants and Convertibles, Integrated Topics in Managerial Finance, Index.
Fundamental Concepts of Managerial Finance, The Finance Function, Financial Statements, The Financial Environment, The Tax Environment, The Time Dimension in Financial Decisions, The Time Value of Money, Capital Budgeting Techniques, How the Market Determines Discount Rates, Financial Analysis and Planning and Control, Financial Ratio Analysis, Financial Planning and Control, Financial Forecasting, Working Capital Management, Working Capital Policy, Cash and Marketable Securities Management, Inventory Management, Credit Management and Policy, Short-Term Financing, Decision Making Under Uncertainty, Risk and Return: Theory and Evidence and Applications, Options on Risky Assets, Cost of Capital and Valuation, Financial Structure and the Cost of Capital, Capital Structure and the Cost of Capital, Valuation, The Treasurer's Point of View: Policy Decisions, Common Stock Financing, Lease Financing, Warrants and Convertibles, Integrated Topics in Managerial Finance, Index.